Silajathu Rasayana in Management of Rheumatoid Arthritis (International Journal of Ayurveda and Pharma Research, 2024)
Rheumatoid Arthritis is a systemic autoimmune disease characterized by inflammatory arthritis and extra-articular involvement. Considering the pathophysiology, clinical features, and extra-articular manifestations it can be correlated to Vataraktha in Ayurveda. In this case, a 24-year-old female patient who was diagnosed with Juvenile Rheumatoid Arthritis at the age of 15 and was under Disease-modifying anti-rheumatic drug therapy for several years, complaints of pain and swelling over symmetrical joints of upper and lower limbs along with morning stiffness, and evident boutonniere deformity. She also had pain in her left hip for 4 years. Ayurvedic treatment was initiated with a primary focus on Amapachana, Shodhana, and Rasayana therapies. Patient assessment was conducted using a Visual analog scale, DAS28 score, HAQ-DI score, and Ama assessment tool on the 0th and 69th day. DAS 28 score improved from 7.73 to 3.19, and HAQ-DI score improved from 1.63 to 0.88. The visual analog scale was improved from 8 to 4. Following 69 days of treatment incorporated with Ayurvedic treatment procedures coupled with Rasayana therapy, demonstrated a notable amelioration of symptoms, an enhancement in the overall quality of life, and an improvement in laboratory parameters.